Relations préconjugales, fidélité, suicides: conduites sexuelles dans un groupe de Lapons nomades - Delaporte, Yves; Roué, Michèle (Anthropologica, 2022)
The purpose of this paper is to describe the sexual behaviour in a Lapp nomadic group, relatively preserved as far as acculturation is concerned. The authors hope to reveal that christian ideology has had very little influence on the sexual behaviour of the Lapps. This one is a coherent entity, integrated within specific Lapp culture. Suicide, resulting from an unfortunate love-affair, expresses several features of Lapp social structure in a most dramatic way: bilateralism, woman's high status.